A 12-Week Evidence-Based Education Project to Reduce Cardiovascular and Metabolic Risk in Adults With Serious Mental Illness in the Integrated Care Setting. (March 2021) - Fenton, Ashley; Sharps, Phyllis; Kverno, Karan; RachBeisel, Jill; Gorth, Marsha
BACKGROUND: Individuals with serious mental illness (SMI) such as schizophrenia spectrum disorders, severe bipolar disorder, or severe recurrent major depressive disorder have a shorter life expectancy compared with those in the general population. This is largely due to the higher rates of diabetes, hyperlipidemia, and hypertension. Treatment adherence, diet, exercise, and weight management are modifiable risk factors for these cardiometabolic conditions, yet the use of educational lifestyle interventions is not common practice in the clinical setting.AIM: The purpose of this project was to evaluate a 12-week evidence-based diabetes prevention education program integrated into a primary care behavioral health setting for adults with SMI, diabetes, or prediabetes, and who were overweight or obese.METHOD: This project utilized a pretest–posttest intervention design. Outcomes for this project included diabetes knowledge, self-care, and health indicators (blood pressure, hemoglobin A1C, weight, body mass index, and medication adherence). The project also addressed feasibility and acceptability of the program in this setting.RESULTS: Project outcomes showed a reduction in weight, waist circumference, hemoglobin A1C, and blood pressure. Outcomes also indicated an improvement in participants' self-knowledge and self-care.CONCLUSIONS: There was a high attendance rate and overall acceptability and feasibility described by participants. This project highlights the important role that primary care providers can play in providing health education to patients with SMI.